Detection of Chromium (Cr) and Lead (Pb) in Marine Sediments and its Bioaccumulation in Holothuria leucospilota (Sea Cucumber) in Jasaan, Misamis Oriental, Philippines - Nagac, Clariza; Jardin, Juan Carlo; Salem, Eduard; Canencia-Badilla, Mae Oljae (Indonesian Journal of Social and Environmental Issues (IJSEI), 2024)
Sea cucumber inhabits shallow waters of the coastal area. Consequently, these organisms are vulnerable to heavy metals through food consumption and direct exposure to sediments, considering that they are filter-feeding and bottom-dwelling organisms. Holothuria. leucospilota, locally known as “balat” is used as a bioindicator to measure environmental pollution in this study. The analysis of Cr and Pb were administered in the sediments and the body wall of H. leucospilota from residential and commercial areas along the coastal area of Jasaan, Misamis Oriental. Cr and Pb concentrations were determined using the Atomic Absorption Spectroscopy (AAS) method for sediments and the Graphite Furnace Atomic Absorption Spectroscopy (GFAAS) method for H. leucospilota. Results of the concentration of heavy metals in the sediments and body wall of H. leucospilota revealed that Cr>Pb while Pb>Cr in residential and commercial areas, respectively. The results of Cr and Pb concentration in the body wall of H. leucospilota were compared to the standard set by WHO/EPA and CODEX. Thus, H. leucospilota collected in the areas exceeded the permissible limit for Cr while Pb in H. leucospilota recorded below the permissible limit. Hence, this implies that this type of food is not safe for food intake and therefore, not recommended for human consumption.